2016
DOI: 10.2147/ijn.s116288
|View full text |Cite
|
Sign up to set email alerts
|

Real-time colorimetric detection of DNA methylation of the <em>PAX1</em> gene in cervical scrapings for cervical cancer screening with thiol-labeled PCR primers and gold nanoparticles

Abstract: Background DNA methylation can induce carcinogenesis by silencing key tumor suppressor genes. Analysis of aberrant methylation of tumor suppressor genes can be used as a prognostic and predictive biomarker for cancer. In this study, we propose a colorimetric method for the detection of DNA methylation of the paired box gene 1 ( PAX1 ) gene in cervical scrapings obtained from 42 patients who underwent cervical colposcopic biopsy. Methods A thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…GSEA results further confirmed the identified pathways and simultaneously found some new biological processes DEGs significantly enriched such as RNA splicing and Gene silencing 72, 73. Mole S, et al demonstrated that HPV16 E2 as a transcription factor could regulate the expression of RNA splicing factors SF2/ASF, SRp20 and SC35 to facilitate cervical cancer progression 74.…”
Section: Discussionmentioning
confidence: 76%
“…GSEA results further confirmed the identified pathways and simultaneously found some new biological processes DEGs significantly enriched such as RNA splicing and Gene silencing 72, 73. Mole S, et al demonstrated that HPV16 E2 as a transcription factor could regulate the expression of RNA splicing factors SF2/ASF, SRp20 and SC35 to facilitate cervical cancer progression 74.…”
Section: Discussionmentioning
confidence: 76%
“…One is GynTect ® produced by Oncgnostics company of German and another is QIAsure ® by QIAGEN and Self-screen BV company. According to the product specifications for GynTect ® 22,23 The cycle threshold (Ct) values for each target were normalized for DNA input. The values for all samples were transformed into relative quantity.…”
Section: Discussionmentioning
confidence: 99%
“…The methylation of APC1A promoter was also closely correlated with biological features in CC and could therefore be used to predict poor prognosis of CC [34]. DNA methylation could result in carcinogenesis through silencing important tumor suppressor genes and aberrant methylation of tumor suppressor genes could be regarded as a prognostic and predictive biomarker for cancer [35]. An increase in the promotor methylation of Ezrin in CC cases would normally cause a decrease in gene transcription.…”
Section: Discussionmentioning
confidence: 99%